Physical Characteristics of the Internal Limiting Membrane and their Significance in Ocular Surgery and Beyond (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Efforts to render surgical removal of the internal limiting membrane safer and easier depend on an in-depth understanding of its physical characteristics.Purpose: Studying the internal limiting membrane is particularly gratifying, as it represents the most easily accessible of all human basement membranes and many findings may contribute to an improved comprehension of human basement membranes in general.Data sources: MEDLINE with no language restriction through March 2014. Data selection: Overview of recent research results from the authors own study group as well as a context of the current literature.Conclusion: New examination techniques such as chromaticity analysis and trans-lational use of established techniques like atomic force microscopy allow new insights into mechanical properties of the internal limiting membrane. Chromaticity analysis permits objective measurements of the contrast behavior of the internal limiting membrane when exposed to vital dyes. Compared to various approved dyes, indocyanine green shows the best visible contrast, in accordance with its popularity despite its off-label status. Atomic force microscopy allows the examination of the native internal limiting membrane. It, thus, enabled the study group to provide an extensive topographic map including surface structure, thickness and stiffness, avoiding the fixation artifacts of previous descriptions. Surface structure, stiffness, rolling behavior and cell adhesion were found to be asymmetrical between the two opposite surfaces of the membrane and the same asymmetry could be reproduced for several other ocular basement membranes challenging the current model of basement membrane ultrastructure.
Keywords: Atomic force microscopy; brilliant blue G; chromaticity analysis; chromovitrectomy; indocyanine green; internal limiting membrane; trypan blue; vital dyes